PENGARUH ANGKA HARAPAN HIDUP, KEMISKINAN DAN RATA-RATA LAMA SEKOLAH TERHADAP IPM DI PROVINSI DI YOGYAKARTA - M. Zuhriadi; Dhea Amanda; Syarifah; Khairani Alawiyah Matondang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research on the influence of life expectancy, poverty, and average years of schooling on the Human Development Index (HDI) in DI Yogyakarta Province shows that poverty has a negative influence on the level of the human development index, while life expectancy and average years of schooling have an effect. positive towards HDI. The research results also show that the highest contribution to HDI is life expectancy, followed by average years of schooling. Another study found that the variables average length of schooling, per capita expenditure, and unemployment simultaneously had a significant effect on HDI. The research method used is panel data regression analysis and quantitative methods with a descriptive approach. The results of this research can be a reference in formulating development policies in DI Yogyakarta Province.